Reduction in the QRS area after cardiac resynchronization therapy is associated with survival and echocardiographic response - Ghossein, Mohammed A; van Stipdonk, Antonius M W; Plesinger, Filip; Kloosterman, Mariëlle; Wouters, Philippe C; Salden, Odette A E; Meine, Mathias; Maass, Alexander H; Prinzen, Frits W; Vernooy, Kevin (Journal of cardiovascular electrophysiology, 2021)
INTRODUCTION: Recent studies have shown that the baseline QRS area is associated with the clinical response after cardiac resynchronization therapy (CRT). In this study, we investigated the association of QRS area reduction (∆QRS area) after CRT with the outcome. We hypothesize that a larger ∆QRS area is associated with a better survival and echocardiographic response. METHODS AND RESULTS: Electrocardiograms (ECG) obtained before and 2-12 months after CRT from 1299 patients in a multi-center CRT-registry were analyzed. The QRS area was calculated from vectorcardiograms that were synthesized from 12-lead ECGs. The primary endpoint was a combination of all-cause mortality, heart transplantation, and left ventricular (LV) assist device implantation. The secondary endpoint was the echocardiographic response, defined as LV end-systolic volume reduction ≥ of 15%. Patients with ∆QRS area above the optimal cut-off value (62 µVs) had a lower risk of reaching the primary endpoint (hazard ratio: 0.43; confidence interval [CI] 0.33-0.56, p < .001), and a higher chance of echocardiographic response (odds ratio [OR] 3.3;CI 2.4-4.6, p < .0001). In multivariable analysis, ∆QRS area was independently associated with both endpoints. In patients with baseline QRS area ≥109 µVs, survival, and echocardiographic response were better when the ∆QRS area was ≥62 µVs (p < .0001). Logistic regression showed that in patients with baseline QRS area ≥109 µVs, ∆QRS area was the only significant predictor of survival (OR: 0.981; CI: 0.967-0.994, p = .006). CONCLUSION: ∆QRS area is an independent determinant of CRT response, especially in patients with a large baseline QRS area. Failure to achieve a large QRS area reduction with CRT is associated with a poor clinical outcome.
Keywords: výsledek terapie; Stroke Volume; Electrocardiography; survival; Cardiac Resynchronization Therapy; retrospektivní studie; heart failure; srdeční selhání; QRS area reduction; QRS area; echocardiographic response; Echocardiography; tepový objem; echokardiografie; Treatment Outcome; lidé; Heart Failure; Humans; srdeční resynchronizační terapie; Retrospective Studies; cardiac resynchronization therapy; elektrokardiografie